Towards holomorphology in entomology: rapid and cost‐effective adult–larva matching using NGS barcodes. (2nd April 2018) - Yeo, Darren; Puniamoorthy, Jayanthi; Ngiam, Robin Wen Jiang; Meier, Rudolf
Abstract: In many taxa the morphology of females and immatures is poorly known because species descriptions and identification tools have a male bias. The root causes are problems with matching life‐history stages and genders belonging to the same species. Such matching is time‐consuming when conventional methods are used (e.g. rearing) and expensive when the stages are matched with DNA barcodes. Unfortunately, the lack of associations is not a trivial problem because it renders a large part of the phenome of insects unexplored, although larvae and females are useful sources of characters for descriptive and phylogenetic purposes. In addition, many collectors intentionally avoid females and immature stages, which skews survey results, interferes with collecting life‐history information, and makes it less likely that rare species are discovered. These problems even exist for well‐studied taxa like Odonata, where obtaining adult–larva matches relies largely on rearing. Here we demonstrate how the matching problem can be addressed with cost‐effective tagged amplicon sequencing of a 313‐bp segment of cox1 with next‐generation sequencing (NGS) ('NGS barcoding'). We illustrate the value of this approach based on Singapore's odonate fauna which is of a similar size as the European fauna (Singapore, 122 extant species; Europe, 138 recorded species). We match the larvae and adults of 59 species by first creating a barcode database for 338 identified adult specimens representing 83 species. We then sequence 1178 larvae from a wide range of sources. We successfully barcode 1123 specimens, which leads to adult–larva matches for 59 species based on our own barcodes (55) and online barcode databases (4). With these additions, 84 of the 131 species recorded in Singapore have now been associated with a species name. Most common species are now matched (83%), and good progress has been made for vulnerable/near‐threatened (55%), endangered (53%), and critically endangered species (38%). We used nondestructive DNA extraction methods in order to be able to use high‐resolution imaging of matched larvae to establish a publicly available digital reference collection for odonates which is incorporated into 'Biodiversity of Singapore' (https://singapore.biodiversity.online/ ). We suggest that the methods described here are suitable for many insect taxa because NGS barcoding allows for fast and low‐cost matching of well‐studied life‐history stages with neglected semaphoronts (eggs, larvae, females). We estimate that the specimen‐specific amplicons in this study ( c . 1500 specimens) can now be obtained within eight working days and that the laboratory and sequencing cost is c . US600 (< US0.40 per specimen). Abstract : The present study demonstrates how next‐generation sequencing (NGS) barcodes can quickly ( c . 8 days) associate large numbers of insect larvae (> 1100) and adults (> 300) at low cost ( c . US600, i.e. < US0.40 per specimen). The study matches larvae and adults for 59 species so that two‐thirds of all Odonata species in Singapore now have known larvae; larval morphology is illustrated in the digital reference collection (https://singapore.biodiversity.online ). These findings suggests that eggs, larvae and females should be sampled more aggressively because they can yield significant new morphological and natural history information after association with NGS barcodes.